2013
DOI: 10.1021/bi400952m
|View full text |Cite
|
Sign up to set email alerts
|

A Large Solvent Isotope Effect on Protein Association Thermodynamics

Abstract: Solvent reorganization can contribute significantly to the energetics of protein:protein interactions. However, our knowledge of the magnitude of the energetic contribution is limited, in part, by a dearth of quantitative experimental measurements. The biotin repressor forms a homodimer as a prerequisite to DNA binding to repress transcription initiation. At 20°C the dimerization reaction, which is thermodynamically coupled to binding of a small ligand, bio-5'-AMP, is characterized by a Gibbs free energy of -7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…First, measurements of wtBirA dimerization performed in H 2 O and D 2 O over a range of temperatures indicate that solvent release is the major thermodynamic driving force for dimer formation. 32 The large unfavorable dimerization enthalpy reflects the penalty associated with the removal of solvent from the protein surface, and the correspondingly large favorable entropy, −TΔS°, arises from the release of this solvent to the bulk. Second, consistent with solvent release also serving as the major driving force for BirA variant dimerization, the solvent isotope effect measured at 20 °C is identical for wtBirA and variants regardless of the location of the alanine substitution.…”
Section: ■ Discussionmentioning
confidence: 99%
“…First, measurements of wtBirA dimerization performed in H 2 O and D 2 O over a range of temperatures indicate that solvent release is the major thermodynamic driving force for dimer formation. 32 The large unfavorable dimerization enthalpy reflects the penalty associated with the removal of solvent from the protein surface, and the correspondingly large favorable entropy, −TΔS°, arises from the release of this solvent to the bulk. Second, consistent with solvent release also serving as the major driving force for BirA variant dimerization, the solvent isotope effect measured at 20 °C is identical for wtBirA and variants regardless of the location of the alanine substitution.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A more recent study of D 2 O effects in the biotin repressor found water reorganization was important in protein dimerization [42]. In studying binding of DNA to the cAMP repressor protein·cAMP complex, Shi et al found a more positive enthalpy in D 2 O than H 2 O [43].…”
Section: 1 Thermodynamic Solvent Isotope Effectsmentioning
confidence: 99%
“…Thus, the effect of the H 2 O/D 2 O exchange on the B-A transition is relatively small. Large effects resulting from an H 2 O/D 2 O exchange have been reported in the literature for protein stability, dynamics and association (Cioni and Strambini 2002 ; Sasisanker et al 2004 ; Eginton and Beckett 2013 ). Recent simulations on a RNA hairpin (Pathak and Bandyopadhyay 2017 ) indicate a large effect induced by an H 2 O/D 2 O exchange on its thermal stability.…”
Section: Discussionmentioning
confidence: 87%